A Faster External Sorting Algorithm Using No Additional Disk Space - Islam, Md. Rafiqul; Md. Sap, Mohd. Noor; Sarker, Md. Sumon; Islam, Sk. Razibul (Penerbit UTM Press, 2006)
The effective performance of the external sorting is analyzed in terms of both time and I/O complexities. This paper is concerned with a more efficient external sorting algorithm, where both the time and I/O (read and write) complexities have been reduced. The proposed method is a hybrid technique that uses quick sort and merge sort in two distinct phases. Both the time and I/O complexities of the proposed algorithm are analyzed here and compared with the complexities of the existing similar algorithms. The proposed algorithm uses special in-place merging technique, which creates no extra backup file for manipulating huge records. For this, the algorithm saves huge disk space, which is needed to hold the large file. This also reduces time complexity and makes the algorithm faster.